Identification and characterization of a novel CASR mutation causing familial hypocalciuric hypercalcemia - Lin, Chien-Ming; Ding, Yi-Xuan; Huang, Shih-Ming; Chen, Ying-Chuan; Lee, Hwei-Jen; Sung, Chih-Chien; Lin, Shih-Hua (Frontiers in Endocrinology, 2024)
Context: Although a monoallelic mutation in the calcium-sensing receptor (CASR) gene causes familial hypocalciuric hypercalcemia (FHH), the functional characterization of the identified CASR mutation linked to clinical response to calcimimetics therapy is still limited.Objective: A 45-year-old male presenting with moderate hypercalcemia, hypocalciuria, and inappropriately high parathyroid hormone (PTH) had a good response to cinacalcet (total serum calcium (Ca 2+ ) from 12.5 to 10.1 mg/dl). We identified the genetic mutation, characterized the functional and pathophysiological mechanisms, and linked it to calcimimetics treatment in vitro.Design: Sanger sequencing of CASR, GNA11, and AP2S1 genes was performed in his family.The simulation model was used to predict the function of identified mutant. The in vitro studies including immunoblotting, immunofluorescence, cycloheximide chase study, Calbryte™ 520 Ca 2+ detection, and half-maximal effective concentration (EC50) were examined.Results: This proband was found to carry a de novo heterozygous missense I554N in the cysteine-rich domain of CASR, which was pathogenic based on the different software prediction models and ACGME criteria. The simulation model showed CASR I554N mutation decreased its binding energy with Ca 2+ . Human CASR I554N mutation attenuated the stability of CASR protein, reduced the expression of p-ERK 1/2, and blunted the intracellular Ca 2+ response to gradient extracellular Ca 2+ (eCa 2+ ) concentration. The EC50 study also demonstrated the correctable effect of calcimimetics on the function of the CASR I554N mutation.This novel CASR I554N mutation causing FHH attenuates CASR stability, its binding affinity with Ca 2+ , and the response to eCa 2+ corrected by therapeutic calcimimetics.